Kelimpahan Populasi Spesies Lalat Buah (Diptera : Tephritidae) Pada Pertanaman Jeruk di Ogan Ilir, Sumatera Selatan - Elfin Meidi; Yanse Masliana Pakpahan; Nadia Nadia; Yuana Yuana; Desriza Rahma Dani; Yunita Nurfadila; Mukri Purnama Nasution; Abu Umayah; Bambang Gunawan; Arsi Arsi (xxxx-xxxx, 2023)
Meidi E, Pakpahan YM, Nadia N, Yuana Y, Dani DR, Nurfadila Y, Nasution MP, Umayah A, Gunawan B, Arsi A.  2022. Population abundance of fruit fly species (Diptera : Tephritidae) on citrus plantation in Ogan Ilir, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 607-613. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Citrus plants Ogan Ilir Regency is one of the areas producing horticultural crops and fruits, including citrus fruits (Citrus sp). Citrus plants are attacked by pests caused by fruit flies (Bactrocera sp). The purpose of this study was to determine the population and abundance of fruit flies (Bactrocera sp) on citrus plants. Sampling was carried out randomly (random sampling) using a hanging bottle trap that was installed for 1x24 hours. The results of the field research showed that fruit flies on citrus plants in Timbangan Village, Palem Raya, and Tanjung Pering found one species, namely Bactrocera dorsalis The results of this observation showed a decrease in the population of B. dorsalis and in each sampling. The highest individual population was found in Palem Raya Village, while the lowest population was found in Tanjung Pering Village. The population of fruit flies in test 1 contained 569 fruit flies, in replicate 2 there were 350 fruit flies, and in replicate 3 there were 327 fruit flies. A total of 1,246 B. dorsalis in Timbangan, Palem Raya, and Tanjung Pering villages were trapped. The conclusion from this observation is that B. dorsalis is a species of fruit fly found in citrus plantations in the villages of Timbangan, Palem Raya, and Tanjung Pering and the average population is 415 fruit flies. The use of hanging bottle traps as traps is an effective solution in controlling individual populations of fruit flies on citrus plant.